Reform and efficiency of New Zealand's airports. (October 2015) - Abbott, Malcolm
Abstract: The paper analyses the efficiency performance of New Zealand's airports in the context of structural reform. This study is in two parts using two separate databases. In the first part a Malmquist Data Envelopment Analysis approach is used to estimate the productivity change over the longer term of the country's three largest airports between 1991/92 and 2011/12. Partial productivity indicators are used to supplement and reinforce this analysis. In the second part, a separate database is used with Data Envelopment Analysis in a two-stage process to determine the impact of scale economies and ownership type on levels of efficiency. The first part of the study found that the efficiency and productivity of the three airports improved over the years, although this was influenced to some degree by locational factors. The second part of the study found that the larger airports were more efficient than the smaller ones, and jointly owned airports are somewhat less efficient. Productivity gains appear to enable airport expansion, rather than price reductions.